Attendance in Adult Day Care Centers of Cognitively Intact Older Persons: Reasons for Use and Nonuse. (August 2013) - Iecovich, Esther; Biderman, Aya
The article aims to (a) examine the reasons for nonuse of ADCC, and (b) explore the reasons for use of adult day care centers (ADCCs) among users. The sample includes 819 respondents of whom 417 are users of 13 day care centers and 402 are nonusers, matched by age, gender, and family physician in the southern region of Israel. Data collection includes interviews that used a structured questionnaire. The most frequent reasons for nonuse of ADCCs are accessibility barriers, characteristics of participants and of the ADCCs, "no need for this service, " and personal difficulties. Those who use this service report that it improved their well-being, met their needs, enabled them to establish social relationships, and alleviated their family caregivers' burden. ADCCs should be more responsive to the needs of various constituencies of frail older adults and be more accessible to those who do not use this type of service.